PENJAMINAN MUTU PENDIDIKAN DENGAN ISO 9001:2008 : (Studi Kasus di SMP Negeri Jakarta) - Herlina (Jurnal Visipena, 2017)
The objective of this research is to comprehend contribution of ISO 9001:2008 in improving school quality management. It is a qualitative research with a case study method conducted in Jakarta State Junior High School.The data were collected through participant observation using interview, observation, document study, and recording. The data analysis and interpretation indicates that (1) continuous improvement is a cycle of plan, do, check, and act to achieve quality; (2) work process, teamwork, and communication are needed by team work in achieving the quality; (3) training is held by the school to improve the quality of human resources. Those aspects done effectively since school management of Junior High School implemented ISO 9001:2008. The findings lead to the recommendation that (1) continuous improvement should be done though not monitored by ISO; (2) increasing commitment to team work; (3) monitoring and evaluation on training should be done internally and externally. It is also recommended for education stakeholders to improveaccountability in assessing standard of education.